Experience capitalization: Stronger communities in South East Asia - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2018)
The stories in this booklet come from different teams working in Vietnam, Cambodia, Myanmar, Malaysia, the Philippines, Laos and India, with all of them addressing the main challenges that farmers and the rural communities in this region face. A different context, which provides different challenges to the ones CTA has been working with. These stories, however, show many lessons that are equally applicable in the ACP countries with which we are more familiar. There is an equal need to support indigenous communities, to strengthen local groups, or to recognise the enormous contribution that female farmers make, and to work together with those who are trying innovative and successful approaches. It is equally necessary to carry out a detailed analysis of the context in which these initiatives take place, and to encourage all stakeholders to take part in it.